MINIMIZING CORRUPTION BY OPTIMIZING THE PRIVILEGE OF ACEH (Constitutional Perspective) - Cakra Arbas (Asia Pacific Fraud Journal, 2017)
ABSTRACTEradication of corruption is one way to accelerate national development aimed at realizing justice, prosperity, and order for the Indonesian people as a whole based on Pancasila and 1945 Constitution of the Republic of Indonesia. Aceh has been positioned as a special regional government unit, which is a crystallization of the values contained in the local wisdom of the Acehnese people, such as upholding the principle of divinity in all social activities, including in the scope of local government that always adhere to romantic customs.The Essence of the foundation for preventing corruption, especially in Aceh, has been attempted by establishing organic regulations, such as Qanun (from Acehnese language means legislation). Substantially, however, the organic regulations are sometimes not directly addressed to the term of corruption. Therefore, it is necessary to formulate regulation as an effort to accommodate the eradication of criminal acts of corruption. On the same occasion, the synergy of customary institutions as the lowest level of local government unit becomes a necessity, especially Imeum Mukim (from Acehnese language means head of customary government). Imeum Mukim can serve as a locomotive to prevent corruption by strengthening his integrity and competence.The research method used is normative legal research. The type of data used is secondary data, consisting of primary legal material (various forms of legislation), secondary legal materials (data collection of scientific work of scholars and the results of the research relating to the privilege of Aceh Province), and tertiary legal materials (materials providing information on primary legal materials and secondary legal materials, such as dictionaries and encyclopedias). Once the data are collected and considered to be complete enough, the next step is to manage and analyze the data. Data analysis is conducted using qualitative data analysis technique.